2020
DOI: 10.1371/journal.pone.0242440
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pulse oximetry and Integrated Management of Childhood Illness (IMCI) training on antibiotic prescribing practices in rural Malawi: A mixed-methods study

Abstract: Background The misdiagnosis of non-malarial fever in sub-Saharan Africa has contributed to the significant burden of pediatric pneumonia and the inappropriate use of antibiotics in this region. This study aims to assess the impact of 1) portable pulse oximeters and 2) Integrated Management of Childhood Illness (IMCI) continued education training on the diagnosis and treatment of non-malarial fever amongst pediatric patients being treated by the Global AIDS Interfaith Alliance (GAIA) in rural Malawi. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…All studies enrolled children aged <15 years. Six studies included, but not exclusively, patients <2 months old [23][24][25][26][27][28] ; another enrolled only those in this age group. 29 Seven studies included patients aged 2 months to ≤5 years, 23-28 30-32 and only two included children >5 years and adolescents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies enrolled children aged <15 years. Six studies included, but not exclusively, patients <2 months old [23][24][25][26][27][28] ; another enrolled only those in this age group. 29 Seven studies included patients aged 2 months to ≤5 years, 23-28 30-32 and only two included children >5 years and adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…25 26 28 Staff should be given appropriate and ongoing training not just in the mechanics of pulse oximetry but also in its use in syndromic diagnosis and clinical management, thus building patient and caregiver trust in their clinical decision-making 23 26 28 29 32 41 42 ; largerscale benefits, such as better antibiotic stewardship may follow. 23 Fourth, pulse oximetry should not be rolled out in isolation if its full potential to improve the care of acutely febrile patients in LMICs is to be realised. Rather, it must be part of a systems approach incorporating reliable access to supplemental oxygen as well as strengthening of health infrastructure, sustainable provision of context-appropriate equipment and staff training, and continuous and comprehensive quality improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived improved confidence in the clinical decision making of clinical officers and nurses after pulse oximetry and specialty-specific training has also been seen in Malawi among healthcare workers caring for children with suspected pneumonia. [ 20 ] However, education alone may not be enough to improve confidence and a thoughtful approach to setting and context and clinical role within the healthcare team need to be considered for future education capacity building initiatives. [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have demonstrated the utility of pulse oximetry in clinical decision‐making by identifying severely ill young children with community‐acquired pneumonia by primary health workers in sub‐Saharan Africa [ 13 , 14 , 15 ], as well as reducing likely inappropriate antibiotic prescription. Among the reasons for the latter are increased diagnostic confidence and improved management of patient and/or caregiver expectations through demonstration of objective physiological measurements [ 16 ].…”
Section: Introductionmentioning
confidence: 99%